Delves Microsampling System in use with Perkin-Elmer atomic absorption spectrophotometer - Perkin-Elmer Corporation (1970)
General view of an unidentified chemist using a Perkin-Elmer Model 403 Atomic Absorption Spectrophotometer, in conjunction with the Delves Microsampling System, to test the lead content of a child's blood sample. Per notations accompanying the photograph, the laboratory depicted is associated with the Department of Human Resources located in Washington, D.C. Devised by Dr. H. Trevor Delves, the Delves system enabled mass screening for lead in the blood at the rate of 50 samples per hour, a significant increase over previous standard methods.
Keywords: Atomic absorption spectroscopy; Employees; Perkin-Elmer Corporation; Scientific apparatus and instruments; Blood--Analysis; Chemists; Corporations; Lead--Testing; Laboratories